Genome-wide linkage and association study implicates the 10q26 region as a major genetic contributor to primary nonsyndromic vesicoureteric reflux. Issue 1 (December 2017) - Darlow, John; Darlay, Rebecca; Dobson, Mark; Stewart, Aisling; Charoen, Pimphen; Southgate, Jennifer; Baker, Simon; Xu, Yaobo; Hunziker, Manuela; Lambert, Heather; Green, Andrew; Santibanez-Koref, Mauro; et al.
Abstract Vesicoureteric reflux (VUR) is the commonest urological anomaly in children. Despite treatment improvements, associated renal lesions – congenital dysplasia, acquired scarring or both – are a common cause of childhood hypertension and renal failure. Primary VUR is familial, with transmission rate and sibling risk both approaching 50%, and appears highly genetically heterogeneous. It is often associated with other developmental anomalies of the urinary tract, emphasising its etiology as a disorder of urogenital tract development. We conducted a genome-wide linkage and association study in three European populations to search for loci predisposing to VUR. Family-based association analysis of 1098 parent-affected-child trios and case/control association analysis of 1147 cases and 3789 controls did not reveal any compelling associations, but parametric linkage analysis of 460 families (1062 affected individuals) under a dominant model identified a single region, on 10q26, that showed strong linkage (HLOD = 4.90; ZLRLOD = 4.39) to VUR. The ~9Mb region contains 69 genes, including some good biological candidates. Resequencing this region in selected individuals did not clearly implicate any gene butFOXI2, FANK1 andGLRX3 remain candidates for further investigation. This, the largest genetic study of VUR to date, highlights the 10q26 region as a major genetic contributor to VUR in European populations.